Alonso Cano y el retablo de San Francisco en la Iglesia de Santiago de Madrid - Díaz Moreno, Félix (Anales de Historia del Arte, 2008)
The parish of Santiago in Madrid, hoarded throughout his expanded to history important art works, among them emphasized the altarpiece dedicated to San Francisco. The images that conformed it were made by Alonso Cano; the appearance of data related to the same ones, provides a new vision on the process of creation and its chronology.